Systemic therapy for vulval Erosive Lichen Planus (the 'hELP' trial): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Simpson, Rosalind; Murphy, Ruth; Bratton, Daniel; Sydes, Matthew; Wilkes, Sally; Nankervis, Helen; Dowey, Shelley; Thomas, Kim
Abstract Background Erosive lichen planus affecting the vulva (ELPV) is a relatively rare, chronic condition causing painful raw areas in the vulvovaginal region. Symptoms are pain and burning, which impact upon daily living. There is paucity of evidence regarding therapy. A 2012 Cochrane systematic review found no randomised controlled trials (RCTs) in this field. Topically administered corticosteroids are the accepted first-line therapy: however, there is uncertainty as to which second-line treatments to use. Several systemic agents have been clinically noted to show promise for ELPV refractory to topically administered corticosteroids but there is no RCT evidence to support these. The 'hELP' study is a RCT with an internal pilot phase designed to provide high-quality evidence. Methods/Design The objective is to test whether systemic therapy in addition to standard topical therapy is a beneficial second-line treatment for ELPV. Adjunctive systemic therapies used are hydroxychloroquine, methotrexate, mycophenolate mofetil and prednisolone. Topical therapy plus a short course of prednisolone given orally is considered the comparator intervention. The trial is a four-armed, open-label, pragmatic RCT which uses a blinded independent clinical assessor. To provide 80 % power for each comparison, 96 participants are required in total. The pilot phase aims to recruit 40 participants. The primary clinical outcome is the proportion of patients achieving treatment success at 6 months. 'Success' is defined by a composite measure of Patient Global Assessment score of 0 or 1 on a 4-point scale plus improvement from baseline on clinical photographs scored by a clinician blinded to treatment allocation. Secondary clinical outcomes include 6-month assessment of: (1) Reduction in pain/soreness; (2) Global assessment of disease; (3) Response at other affected mucosal sites; (4) Hospital Anxiety and Depression Scale scores; (5) Sexual function; (6) Health-related quality of life using 'Short Form 36' and 'Skindex-29' questionnaires; (7) Days of topical steroid use; (8) Treatment satisfaction; (9) Discontinuation of medications due to treatment failure; (10) Per participant cost of intervention in each treatment group. Adverse events will also be reported. Discussion 'hELP' is the first RCT to address second-line treatment of ELPV. The trial has encountered unique methodological challenges and has required collaborative efforts of the UK Dermatology Clinical Trials Network alongside expert clinicians. Trial registration: current controlled trials ISRCTN 81883379 . Date of registration 12 June 2014.